Triiodothyronine Radioimmunoassay - Lieblich, Jeffrey (1972)
Highly specific antisera to triiodothyronine (T(3)) were prepared by immunization of rabbits with T(3)-bovine serum albumin conjugates. Antisera with T(3) binding capacity of up to 600 ng/ml were obtained. The ability of various thyronine derivatives to inhibit the binding of T(3-)(125)I to anti-T(3) serum was found to vary considerably. l-T(3), d-T(3) and several triiodoanalogues were potent inhibitors of the reaction. Little inhibition of T(3-)(125)I binding was produced by l-thyroxine (T(4)) or other tetraiodo- analogues, thyronine or iodotyrosines. Chromatography of several T(4) preparations indicated that most of their very slight activity could be ascribed to contamination with T(3). Successful assay of T(3) in serum was accomplished by the addition of diphenylhydantoin to the assay system. Under these circumstances, recovery of T(3) added to serum was excellent, and addition of T(4) was without significant effect. Serum T(3) concentrations in normal subjects averaged 145 ±25 ng/100 ml (sd). Increased concentrations (429 ±146 ng/100 ml) were observed in hyperthyroid patients whereas those with hypothyroidism had serum T(3) levels of 99 ±24 ng/100 ml. Elevated T(3) concentrations were found also in hypothyroid patients receiving 25 μg or more of T(3) daily and in those receiving 300 μg of T(4) daily. Serial measurements of T(3) concentrations in subjects after oral T(3) administration revealed peak T(3) concentrations 2-4 hr after T(3) administration. Intramuscular administration of thyrotropin (TSH) resulted in earlier and more pronounced increases in serum T(3) than in serum T(4) concentrations. Triiodothyronine (T(3))(1) was recognized to be a biologically active secretory product of the thyroid gland over a decade ago (1). Recent studies have indicated that it is formed extrathyroidally as well (2, 3). Nevertheless, relatively little information concerning the role of T(3) secretion in different thyroid disorders has been accumulated until very recently. Methods for the measurement of T(3) which require its extraction from plasma, and often its separation from thyroxine as well, have been described by several investigators (4-11). These methods have proven useful, but they are relatively complicated, the number of samples that can be assayed is limited, and they may be affected by in vitro deiodination of thyroxine. More recently the radioimmunoassay technique has been applied to the measurement of T(3). Several preliminary reports have appeared describing the preparation of antibody to triiodothyronine by immunization of animals with T(3)-protein conjugates and its use for the measurement of T(3) in serum (12-15). The present report describes the development of a radioimmunoassay for the measurement of T(3), studies of the specificity of the anti-T(3) serum, and some initial studies which indicate that the method is applicable to the measurement of T(3) in unextracted serum.